Evidence of Chemical Reaction in Binary Blends of Polycarbonate and a Semi-Flexible Liquid Crystal Polymer (Journal of Research Updates in Polymer Science, 2021)
In this study, we provide the experimental results of the binary blends of a semi-flexible nematic liquid crystal polymer (LCP1) and polycarbonate (PC) within their phase diagram. The LCP1/PC blends were investigated by Differential Scanning Calorimetry (DSC), Optical Microscopy (OM), Wide-angle X-Ray Diffraction (WXRD), Fourier Transfer Infrared (FTIR), Gel Permeation Chromatography (GPC), and Nuclear Magnetic Resonance (NMR) techniques and observed the evidence of chemical reaction between LCP1 and PC in their heat-treated blends possibly by transesterification mechanism.